Equity and Value in 'Precision Medicine'. Issue 1 (2nd January 2017) - Gray, Muir; Lagerberg, Tyra; Dombrádi, Viktor
Abstract : Precision medicine carries huge potential in the treatment of many diseases, particularly those with high-penetrance monogenic underpinnings. However, precision medicine through genomic technologies also has ethical implications. We will define allocative, personal, and technical value ('triple value') in healthcare and how this relates to equity. Equity is here taken to be implicit in the concept of triple value in countries that have publicly funded healthcare systems. It will be argued that precision medicine risks concentrating resources to those that already experience greater access to healthcare and power in society, nationally as well as globally. Healthcare payers, clinicians, and patients must all be involved in optimising the potential of precision medicine, without reducing equity. Throughout, the discussion will refer to the NHS RightCare Programme, which is a national initiative aiming to improve value and equity in the context of NHS England.